2021
DOI: 10.3390/nu13072207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing on Gut Microbiota Composition and Functionality for In Vitro Fermentation Experiments

Abstract: The gut microbiota has a profound effect on human health and is modulated by food and bioactive compounds. To study such interaction, in vitro batch fermentations are performed with fecal material, and some experimental designs may require that such fermentations be performed with previously frozen stools. Although it is known that freezing fecal material does not alter the composition of the microbial community in 16S rRNA gene amplicon and metagenomic sequencing studies, it is not known whether the microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Observing similar microbiome signatures in the donors before and after freezing is unsurprising as it is generally accepted that for a variety of human-related samples -including fecal matter (Cardona et al, 2012;Pérez-Burillo et al, 2021), skin and saliva (Marotz et al, 2021;Furuhashi et al, 2022), meconium (Xin et al, 2021), and milk (Lyons et al, 2021) -freezing is sufficient to preserve microbial composition. This is supported by the universal knowledge that low temperatures can slow or stop the proliferation of bacteria already present within samples and hinder the establishment of potential contaminants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing similar microbiome signatures in the donors before and after freezing is unsurprising as it is generally accepted that for a variety of human-related samples -including fecal matter (Cardona et al, 2012;Pérez-Burillo et al, 2021), skin and saliva (Marotz et al, 2021;Furuhashi et al, 2022), meconium (Xin et al, 2021), and milk (Lyons et al, 2021) -freezing is sufficient to preserve microbial composition. This is supported by the universal knowledge that low temperatures can slow or stop the proliferation of bacteria already present within samples and hinder the establishment of potential contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…However, although classified as statistically non-significant, our results still show that there were changes to the microbiome after freezing. Pérez-Burillo et al (2021) have speculated that certain taxa may become impaired due to freezing, allowing competing taxa to thrive in their absence after thawingClick or tap here to enter text.. This change in ecological relations may explain the presence or absence of taxa, such as Deinococcota and Myxococcota phyla, despite the overall stability of the microbiome after freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated the effects of storage conditions on microbiota analysis and reported alterations in Bacteroides abundance, although this has focused on storage conditions while frozen or number of freeze thaw cycles (Pérez-Burillo et al, 2021; Poulsen et al, 2021). Room temperature storage of faecal samples for up to 72 hours has been reported to reduce genus including Bacteroides in adult faecal samples over time (Roesch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that the observed increases in E. coli counts in samples stored at −80 °C may be linked to the differential mortality of other bacterial species in the sample, thus providing E. coli with a competitive advantage. It has been shown that freezing faecal samples may change the bacterial community structure [ 16 ], although some studies have only found marginal changes based on 16S rRNA analyses [ 11 ]. Escherichia coli have been generally described as relatively resilient organisms under different environmental conditions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%